Habari Leo and Mwananchi Newspapers and the Information Dissemination of the 2019 Flood Disaster in Dar es Salaam, Tanzania - Zacharia, Malima Pamba; Mwalo , Innocent (University of Dar es Salaam Library Journal, 2026)
This paper reports the findings of a study that assessed two Kiswahili newspapers in Tanzania, Habari Leo and Mwananchi, for their information dissemination of the 2019 Dar es Salaam flood crisis. They primarily evaluated the extent to which each of the two newspapers was published in Kiswahili, a language widely accessible in this East African nation. They explored the challenges of disseminating flood-disaster information in Tanzania. The study subjected news stories, features, editorials, letters to the editor, and advertisements/PSA published in the two newspapers in April, May, and June 2019. The study found that dissemination in both publications was low, which is inadequate. News reports about flood disasters received the least coverage (0.1%), followed by feature stories (1.25%), editorials (3.75%), and letters to the editor (8.75%) in both newspaper outlets. Compared with Mwananchi, which disseminated three early warning news pieces, three letters to the editor, and one editorial in April 2019, Habari Leo disseminated only one news story and one letter to the editor. The absence of specialised reporters, inadequate infrastructure, uncooperative disaster management agencies, budgetary constraints, and misinformation from flood victims were the leading causes of such limited news dissemination.